2008
DOI: 10.1590/s0103-50532008000600023
|View full text |Cite
|
Sign up to set email alerts
|

High speed synthesis of pyrazolones using microwave-assisted neat reaction technology

Abstract: Descrevemos uma síntese rápida e pratica de pirazolonas, na ausência de solvente, sob irradiação de microondas. Esta metodologia sintética envolve a reação de b-cetoésteres com hidrazinas substituídas e não-substituídas e oferece uma preparação simples e direta de diferentes pirazolonas com alta regioseletividade. Essas pirazolonas podem existir em diferentes formas tautoméricas em solução e o anel 2-aril-pirazol-3-ona permanece torcido em relação ao plano da pirazolona no estado cristalino. O mecanismo da rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Pal et al [63] have also reported the synthesis of a series of pyrazolones 110 (12 examples) from the cyclocondensation reaction of hydrazines 109 with b-ketoesters 108 under solvent-free conditions using MW heating (Scheme 31). Compared to conventional method (in refluxing MeOH for 10 h), MW-assisted reaction completes in 2-4 min in high yield (62-89%).…”
Section: Pyrazolonesmentioning
confidence: 99%
“…Pal et al [63] have also reported the synthesis of a series of pyrazolones 110 (12 examples) from the cyclocondensation reaction of hydrazines 109 with b-ketoesters 108 under solvent-free conditions using MW heating (Scheme 31). Compared to conventional method (in refluxing MeOH for 10 h), MW-assisted reaction completes in 2-4 min in high yield (62-89%).…”
Section: Pyrazolonesmentioning
confidence: 99%
“…The starting materials, 3-methyl-1-substituted-1H-pyrazol-5(4H)-ones (2a-2b), were obtained in high yields as per the method reported (Pal et al, 2008;Kimata et al, 2007) by the treatment of ethyl acetoacetate with 1-phenylhydrazine (1a) or 1-(2,4-dinitrophenyl)hydrazine (1b) using a microwave oven. The 4-acetyl-3-methyl-1-substituted-1H-pyrazol-5(4H)-ones (3a-3b) were prepared by the acylation of (2a-2b) with the corresponding acid chloride following Jensen's procedure (Jensen, 1959).…”
Section: Chemistrymentioning
confidence: 99%
“…General procedure for preparation of 3-methyl-1-(substituted)-1H-pyrazol-5(4H)-one (2a-2b) The 3-methyl-1-(substituted)-1H-pyrazol-5(4H)-one derivatives were prepared as per the reported method and purified by recrystallization from ethanol (Pal et al, 2008;Kimata et al, 2007). …”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the ways by which this functionalization can be achieved is using Mannich or Michael chemistry to introduce the required substituent at position 4 (Scheme 1), but this strategy adds an additional step to the synthesis. Furthermore, dialkylated products can be obtained when Michael addition is used [24][25][26].…”
Section: Introductionmentioning
confidence: 99%